Multimedia Document "Priest Ćira and Priest Spira" - Kovrlija, Darja; Tasić, Valentina; Topalović, Suzana (Infotheca - Journal for Digital Humanities; Vol 13 No 2 (2012): Infotheca - Journal of Informatics and Librarianship, 2024)
Thus students, with the common efforts and cooperation with many cultural institutions, have made closer the book “Priest Ćira and priest Spira” by Stevan Sremac to new generations through multimedia interpretation of less known words and phrases, customs, clothing, housing and a spirit of time presented in the book, as well as a through the multimedia presentation of biography and bibliography of Stevan Sremac.